Facile Solution Synthesis of Quasi‐0D/2D ZnO/CuO and ZnO/CuO/NiO Composites for Improved Photocatalytic Performance. Issue 9 (13th April 2020) - Han, Weining; Luo, Zhanzhou; Zhao, Yi; Li, Jibiao; Li, Ping
Abstract : Heterostructure ZnO/CuO (ZC) and ZnO/CuO/NiO (ZCN) composites are synthesized using a simple solution method. X‐ray diffraction and field‐emission scanning electron microscopy show that quasispherical (0D) monoclinic CuO and/or cubic NiO nanoparticles are found on the surface of the 2D hexagonal ZnO sheets. The photocatalytic properties of the composites in organic pollutant degradation and water splitting can be regulated by adjusting the proportions of Cu/Zn and Ni/Zn added during sample preparation. When ZnO is integrated with high levels of CuO, the binary ZC composites exhibit outstanding photocatalytic performance in degrading methylene blue. Photocatalytic water splitting for H2 production is improved after considerably reducing CuO levels. When ZnO is codoped with low CuO and NiO levels, the photocatalytic performance of ternary ZCN in H2 production is significantly enhanced. Herein, a method for designing ZnO‐based sheet/nanoparticle heterostructures is provided, which are widely used as efficient photocatalysts. Abstract : ZnO/CuO and ZnO/CuO/NiO photocatalysts are synthesized using a simple solution method. The photocatalytic properties of the composites in organic pollutant degradation and water splitting are regulated by adjusting the proportions of Cu/Zn and Ni/Zn added during sample preparation. The improvement of the photocatalytic performance of the composites is mainly due to charge transfer at the interface of the heterojunctions.